Metacognitive awareness and understanding of life meanings as a development factors of sustainable behavior - Belikova Margarita; Pronenko Evgeny (E3S Web of Conferences, 2023)
Continuing to search for the reasons for the alienation of students from education, we turn to the psychology of meaning by D. A. Leont’ev. It is necessary to consider education in the life of students from the point of view of its life meaning for them. In our opinion, the place and role of education in the lives of students can expand the understanding of psychological science about the reasons for their alienation from education. The sought-for relations of the life meaning of learning with metacognitive awareness will complement the view of the mechanism of formation of students' attitude to education. The results obtained indicate that there are significant direct correlations between the life meaningfulness of education for psychology students and their metacognitive awareness. In addition, according to the results of the study, it can be concluded that there is an inverse relationship between the life meaningfulness of education for psychology students and their level of alienation from education.